0% found this document useful (0 votes)
4 views

Unit-3_Resolution Theorem Proving Example

Chapter four discusses resolution theorem proving, a method for proving theorems in propositional or predicate calculus by finding contradictions in a set of clauses. The process involves converting premises into clause form, adding the negation of the goal, and using resolution to derive contradictions, ultimately proving the original goal. Several examples illustrate the application of resolution refutation in different scenarios.

Uploaded by

armaan.singh043
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
4 views

Unit-3_Resolution Theorem Proving Example

Chapter four discusses resolution theorem proving, a method for proving theorems in propositional or predicate calculus by finding contradictions in a set of clauses. The process involves converting premises into clause form, adding the negation of the goal, and using resolution to derive contradictions, ultimately proving the original goal. Several examples illustrate the application of resolution refutation in different scenarios.

Uploaded by

armaan.singh043
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 9

Chapter four: Resolution prepared by: Ismael Abdul Sattar 1

----------------------------------------------------------------------------------------
Resolution theorem proving
Resolution is a technique for proving theorems in the propositional or
predicate calculus that has been a part of AI problem-solving research
from the mid-1960s.
Resolution is the way of finding contradictions in a database of
clauses with minimum use of substitution. Resolution refutation proves a
theorem by negating the statement to be proved and adding this negated
goal to the set of axioms that are known (have been assumed) to be true.
It then uses the resolution rule of inference to show that this leads to a
contradiction. Once the theorem prover shows that the negated goal is
inconsistent with the given set of axioms, it follows that the original goal
must be consistent. This proves the theorem.
Resolution refutation proofs involve the following steps:
1. Put the premises or axioms into clause form.
2. Add the negation of what is to be proved, in clause form, to the set
of axioms.
3. Resolve these clauses together, producing new clauses that logically
follow from them.
4. Produce a contradiction by generating the empty clause.
5. The substitutions used to produce the empty clause are those under
which the opposite of the negated goal (what was originally to be
proven) is true.

Resolution refutation proofs require that the axioms and the negation of
the goal be placed in a normal form called clause form. Clause form
represents the logical database as a set of disjunctions of literals. A literal
is an atomic expression or the negation of an atomic expression.
The most common form of resolution, called binary resolution, is
applied to two clauses when one contains a literal and the other its
negation. If these literals contain variables, the literals must be unified to
make them equivalent. A new clause is then produced consisting of the
disjuncts of all the predicates in the two clauses minus the literal and its
negative instance, which are said to have been “resolved away.” The
resulting clause receives the unification substitution under which the
predicate and its negation are found as “equivalent”.

Producing the Clause Form for Resolution Refutations


The resolution proof procedure requires all statements in the database
describing a situation to be converted to a standard form called clause
form. This is motivated by the fact that resolution is an operator on pairs
of disjuncts to produce new disjuncts. The form the database takes is
referred to as a conjunction of disjuncts. It is a conjunction because all the

1
Chapter four: Resolution prepared by: Ismael Abdul Sattar 2
----------------------------------------------------------------------------------------
clauses that make up the database are assumed to be true at the same
time. It is a disjunction in that each of the individual clauses is expressed
with disjunction (or ∨ ) as the connective.
We now present an algorithm, consisting of a sequence of
transformations, for reducing any set of predicate calculus statements to
clause form.
We demonstrate this process of conjunctive normal form reduction
through an example and give a brief description rationalizing each step.
These are not intended to be proofs of the equivalence of these
transformations across all predicate calculus expressions.
In the following expression, uppercase letters indicate variables (W, X,
Y, and Z); lowercase letters in the middle of the alphabet indicate
constants or bound variables (l, m, and n); and early alphabetic
lowercase letters indicate the predicate names (a, b, c, d, and e). To
improve readability of the expressions, we use two types of brackets: ( )
and [ ], and remove redundant brackets. As an example, consider the
following expression, where X, Y, and Z are variables and l a constant:

1. First we eliminate the → by using the equivalent form proved in


Chapter 2: a → b ≡ ¬ a ∨ b. This transformation reduces the expression
in (i) above:

2. Next we reduce the scope of negation. This may be accomplished using


a number of the transformations like:

Using the fourth equivalences (ii) becomes:

3. Next we standardize by renaming all variables so that variables bound


by different quantifiers have unique names. Because variable names are
“dummies” or “place holders,” the particular name chosen for a variable
does not affect either the truth value or the generality of the clause.
Transformations used at this step are of the form:

2
Chapter four: Resolution prepared by: Ismael Abdul Sattar 3
----------------------------------------------------------------------------------------

Because (iii) has two instances of the variable X, we rename:

4. Move all quantifiers to the left without changing their order. This is
possible because step 3 has removed the possibility of any conflict
between variable names. (iv) now becomes:

After step 4 the clause is said to be in prenex normal form, because all
the quantifiers are in front as a prefix and the expression or matrix
follows after.
5. At this point all existential quantifiers are eliminated by a process
called skolemization. Expression (v) has an existential quantifier for Y.
When an expression contains an existentially quantified variable, for
example, (ƎZ)(foo(…, Z,…)), it may be concluded that there is an
assignment to Z under which foo is true. Skolemization identifies such a
value. Skolemization does not necessarily show how to produce such a
value; it is only a method for giving a name to an assignment that must
exist. If k represents that assignment, then we have foo(…,k,…). Thus:

where the name fido is picked from the domain of definition of X to


represent that individual X. fido is called a skolem constant. If the
predicate has more than one argument and the existentially quantified
variable is within the scope of universally quantified variables, the
existential variable must be a function of those other variables. This is
represented in the skolemization process:

This expression indicates that every person has a mother. Every person is
an X and the existing mother will be a function of the particular person X
that is picked. Thus skolemization gives:

which indicates that each X has a mother (the m of that X). In another
example:

is skolemized to:

3
Chapter four: Resolution prepared by: Ismael Abdul Sattar 4
----------------------------------------------------------------------------------------
The existentially quantified Y and Z are within the scope universally
quantified X but not within the scope of W. Thus each will be replaced by
a skolem function of X. Replacing Y with the skolem function f(X) and Z
with g(X), (v) becomes:

6. Drop all universal quantification. By this point only universally


quantified variables exist (step 5) with no variable conflicts (step 3). Thus
all quantifiers can be dropped, and any proof procedure employed
assumes all variables are universally quantified. Formula (vi) now
becomes:

7. Next we convert the expression to the conjunct of disjuncts form. This


requires using the associative and distributive properties of ∧ and ∨ .
Recall
a ∨ (b ∨ c) = (a ∨ b) ∨ c
a ∧ (b ∧ c) = (a ∧ b) ∧ c
which indicates that ∧ or ∨ may be grouped in any desired fashion. The
distributive property is also used, when necessary. Because
a ∧ (b ∨ c)
is already in clause form, ∧ is not distributed. However, ∨ must be
distributed across ∧ using:
a ∨ (b ∧ c) = (a ∨ b) ∧ (a ∨ c)
The final form of (vii) is:

8. Now call each conjunct a separate clause. In the example (viii) above
there are two clauses:

9. The final step is to standardize the variables apart again. This requires
giving the variable in each clause generated by step 8 different names.

4
Chapter four: Resolution prepared by: Ismael Abdul Sattar 5
----------------------------------------------------------------------------------------
which follows from the nature of variable names as place holders. (ixa)
and (ixb) now become, using new variable names U and V:

Binary resolution proof procedure


The resolution refutation proof procedure answers a query or deduces a
new result by reducing a set of clauses to a contradiction, represented by
the null clause (). The contradiction is produced by resolving pairs of
clauses from the database. If a resolution does not produce a contradiction
directly, then the clause produced by the resolution, the resolvent, is
added to the database of clauses and the process continues.

Example: We wish to prove that “Fido will die” from the statements that
“Fido is a dog” and “all dogs are animals” and “all animals will die.”
Changing these three premises to predicates gives:
Fido is a dog: dog (fido).
All dogs are animals: ∀ (X) (dog (X) → animal (X)).
All animals will die: ∀ (Y) (animal (Y) → die (Y)).
converts these predicates to clause form:
PREDICATE FORM CLAUSE FORM
dog (fido) dog (fido)
∀ (X) (dog) (X) → animal (X)) ¬dog (X) ∨ animal (X)
∀ (Y) (animal (Y) → die (Y)) ¬animal (Y) ∨ die (Y)

Negate the conclusion that Fido will die:


¬die (fido) ¬die (fido)
Resolve clauses having opposite literals, producing new clauses by
resolution as in Figure .This process is often called clashing.
The symbol  in Figure below indicates that the empty clause is produced
and the contradiction found. The  symbolizes the clashing of a predicate
and its negation: the situation where two mutually contradictory
statements are present in the clause space. These are clashed to produce
the empty clause. The sequence of substitutions (unifications) used to
make predicates equivalent also gives us the value of variables under
which a goal is true.

5
Chapter four: Resolution prepared by: Ismael Abdul Sattar 6
----------------------------------------------------------------------------------------

Figure 1: Resolution proof for the "dead dog" problem.

Example 2: We now present an example of a resolution refutation for the


predicate calculus. Consider the following story of the “happy student”:
Anyone passing his history exams and winning the lottery is happy.
But anyone who studies or is lucky can pass all his exams. John did
not study but he is lucky. Anyone who is lucky wins the lottery. Is
John happy?
 First change the sentences to predicate form:
1) Anyone passing his history exams and winning the lottery is happy.
∀ X (pass (X,history) ∧ win (X,lottery) → happy (X))
2) Anyone who studies or is lucky can pass all his exams.
∀ X ∀ Y (study (X) ∨ lucky (X) → pass (X,Y))
3) John did not study but he is lucky.
¬ study (john) ∧ lucky (john)
4) Anyone who is lucky wins the lottery.
∀ X (lucky (X) → win (X,lottery))

6
Chapter four: Resolution prepared by: Ismael Abdul Sattar 7
----------------------------------------------------------------------------------------

 Second changed to clause form


1. ¬pass (X, history) ∨ ¬win (X, lottery) ∨ happy (X)
2. ¬study (Y) ∨ pass (Y, Z)
3. ¬lucky (W) ∨ pass (W, V)
4. ¬study (john)
5. lucky (john)
6. ¬lucky (U) ∨ win (U, lottery)
Into these clauses is entered, in clause form, the negation of the conclusion:
7. ¬happy (john)
The resolution refutation graph of Figure (2) shows a derivation of the
contradiction and, consequently, proves that John is happy.

Figure 2: resolution refutation for the happy student problem.

7
Chapter four: Resolution prepared by: Ismael Abdul Sattar 8
----------------------------------------------------------------------------------------

Example3: As a final example in this subsection we present the “exciting


life” problem; suppose:
All people who are not poor and are smart are happy. Those people
who read are not stupid. John can read and is wealthy. Happy people
have exciting lives. Can anyone be found with an exciting life?

 First change the sentences to predicate form:


We assume ∀ X (smart (X) ≡ ¬ stupid (X)) and ∀ Y (wealthy (Y) ≡ ¬
poor (Y)), and get:

∀ X (¬ poor (X) ∧ smart (X) → happy (X))


∀ Y (read (Y) → smart (Y))
read (john) ∧ ¬ poor (john)
∀ Z (happy (Z) → exciting (Z))
The negation of the conclusion is:
¬ ∃ W (exciting (W))

 Second changed to clause form

poor (X) ∨ ¬ smart (X) ∨ happy (X)


¬ read (Y) ∨ smart (Y)
read (john)
¬ poor (john)
¬ happy (Z) ∨ exciting (Z)
¬ exciting (W)

The resolution refutation for this example is found below Figure (3)

8
Chapter four: Resolution prepared by: Ismael Abdul Sattar 9
----------------------------------------------------------------------------------------

Figure 3: Resolution prove for "exciting life" problem

You might also like